Tax Risk, Tax Avoidance, and Corporate Risk: The Moderating Role of Board Gender in Indonesian Firms - Khaeril Azmi; Baldirc Siregar; Frasto Biyanto; Miswanto Miswanto (LifeSciFi, 2025)
Tax risk and tax avoidance have attracted increasing academic attention due to their implications for corporate risk and governance. This study aims to examine the effect of tax risk and tax avoidance on corporate risk, with gender composition on the board of directors as a moderating variable. Focusing on industrial goods companies listed on the Indonesia Stock Exchange during the 2021–2023 period, this study analyzes 45 observations from 16 companies using panel data regression. Corporate risk is measured by stock return volatility, tax risk is proxied by tax liability uncertainty, and tax avoidance is calculated as the ratio of pre-tax profit to total assets. Gender is measured by the proportion of female directors. The results show that tax risk has a significant negative effect on corporate risk, indicating more prudent management under fiscal uncertainty. Conversely, tax avoidance has a significant positive effect, increasing cash flow volatility and reputation exposure. However, gender does not significantly moderate the relationship between tax avoidance and corporate risk, likely due to low female representation. These findings underscore the importance of fiscally conservative strategies and increasing gender diversity in corporate governance.